Interação e contribuição de incubadora e universidade no desenvolvimento de pequenas empresas - Maehler, Alisson Eduardo (2005)
This work presents the interaction and contribution to business development supported by ITSM Incubator Company and Federal University of Santa Maria (UFSM) to businessmen from small companies of technological base incubated at ITSM Incubator Company. Through a case study of the ITSM and its companies incubated and graduated, we studied what ITSM Incubator Company and UFSM supported and helped about management knowledge to businessmen and their companies. We decided to study that because people at universities and in companies have discussed a lot about enterprise and innovation in recent years. The university has been seen as a good alternative to solve social and economical problems and a source of innovation and competitiveness by the society, specially the business one. The technological incubator is used so that the university and ITSM Incubator Company can increase and qualify their interaction in order to contribute to the creation and maintenance of competitive companies on the market. Through questionnaires and interviews to businessmen and the manager of ITSM and teachers from UFSM, we could notice that ITSM has been succeeded in the development os small business but the University is still limited in relation on the relationship and real contribution to the companies. In order to create more competitive companies at ITSM Company it is necessary to correct some aspects such as the lack of a project of regional development, the strong dependence of ITSM in relation to UFSM and the low interaction of ITSM Incubator Company with its own companies graduated.